Investigation of Single-Wall MoS2 Monolayer Flakes Grown by Chemical Vapor Deposition - Perkgoz, Nihan Kosku; Bay, Mehmet (Nano-Micro Letters, 2015)
Recently, two-dimensional monolayer molybdenum disulfide (MoS2), a transition metal dichalcogenide, has received considerable attention due to its direct bandgap, which does not exist in its bulk form, enabling applications in optoelectronics and also thanks to its enhanced catalytic activity which allows it to be used for energy harvesting. However, growth of controllable and high-quality monolayers is still a matter of research and the parameters determining growth mechanism are not completely clear. In this work, chemical vapor deposition is utilized to grow monolayer MoS2 flakes while deposition duration and temperature effect have been systematically varied to develop a better understanding of the MoS2 film formation and the influence of these parameters on the quality of the monolayer flakes. Different from previous studies, SEM results show that single-layer MoS2 flakes do not necessarily grow flat on the surface, but rather they can stay erect and inclined at different angles on the surface, indicating possible gas-phase reactions allowing for monolayer film formation. We have also revealed that process duration influences the amount of MoO3/MoO2 within the film network. The homogeneity and the number of layers depend on the change in the desorption–adsorption of radicals together with sulfurization rates, and, inasmuch, a careful optimization of parameters is crucial. Therefore, distinct from the general trend of MoS2 monolayer formation, our films are rough and heterogeneous with monolayer MoS2 nanowalls. Despite this roughness and the heterogeneity, we observe a strong photoluminescence located around 675 nm.